Hybrid 3D Printed and Electrospun Multi-Scale Hierarchical Polycaprolactone Scaffolds to Induce Bone Differentiation - Ainhoa Gonzalez-Pujana; Teresa Carranza; Edorta Santos-Vizcaino; Manoli Igartua; Pedro Guerrero; Rosa Maria Hernandez; Koro de la Caba (MDPI AG, 2022)
Complex scaffolds composed of micro- and nano-structures are a key target in tissue engineering and the combination of sequential 3D printing and electrospinning enables the fabrication of these multi-scale structures. In this work, dual 3D printed and electrospun polycaprolactone (PCL) scaffolds with multiple mesh layers were successfully prepared. The scaffold macro- and micro-porosity were assessed by optical and scanning electron microscopy, showing that electrospun fibers formed aligned meshes within the pores of the scaffold. Consequently, the hydrophilicity of the scaffold increased with time, enhancing cell adhesion and growth. Additionally, compression tests in back and forth cycles demonstrated a good shape recovery behavior of the scaffolds. Biological results indicated that hybrid PCL scaffolds are biocompatible and enable a correct cell culture over time. Moreover, MC3T3-E1 preosteoblast culture on the scaffolds promoted the mineralization, increased the alkaline phosphatase (ALP) activity and upregulated the expression of early and late osteogenic markers, namely ALP and osteopontin (OPN), respectively. These results demonstrate that the sequential combination of 3D printing and electrospinning provides a facile method of incorporating fibers within a 3D printed scaffold, becoming a promising approach towards multi-scale hierarchical scaffolds capable of guiding the osteogenic differentiation.